PROJECTS OF RELIGIOUS AUTONOMY OF MUSLIMS OF EUROPEAN RUSSIA, SIBERIA AND THE NORTH CAUCASUS IN THE EARLY 20TH CENTURY - Habutdinov, Ajdar Ur'evic; Imaseva, Marina Maratovna (History, Archeology and Ethnography of the Caucasus, 2022)
The study aims to compare the concepts of religious autonomies of the Muslims of European Russia and Siberia with similar ones in the North Caucasus, set out in projects in the early 20th century. We analyze the process of developing a decision on the creation of religious autonomy for Muslims in European Russia and Siberia and the North Caucasus at the beginning of the 20th century within the framework of a unified Russian statehood, including government bills, drafts of the All-Russian Muslim Congresses in 1906 and 1914, Muslim congresses in the spring-summer of 1917. As a result, in 1917, the Tatar Muslims of Inner Russia and Siberia at the II All-Russian Muslim Congress in July 1917. The concept of national-cultural autonomy was chosen and the Milli Idare and Millet Majlis were established. In the North Caucasus the First Mountain Congress announced the creation of the the Alliance of the United Mountaineers of the North Caucasus and Dagestan (SOGSKD), as a territorial autonomy, with a single body represented by the “Caucasian Muftiate”. We applied the comparative historical method in order to compare the provisions of the projects and characterize the historical events that accompanied their creation. We came to the following conclusions: firstly, the main questions were questions about the form of government and the autonomy of Muslims and the land ussue. Secondly, the political cooperation between the Muslim leaders of the Volga-Ural region and the Caucasus at the beginning of the 20th century led to the creation of the All-Russian party “Ittifaq al-Muslimin”, the Muslim faction of the State Duma, the convocations of the all-Russian Muslim congresses, the idea ofcreating 5 separate Muftiates and a single all-Russian Muslim religious autonomy headed by Sheikh-ul-Islam. Thirdly, in 1917 there was a separation of the two regions on the issues of the formation of religious autonomy, a departure from the idea of common Muslim unity within the borders of Russian statehood. Fourthly, didn’t result in a solution of the issue of organizing the Spiritual Administration of Muslims in the region.
Keywords: Muslims; religious autonomy; national-cultural autonomy; Muslim Congress; sharia; Spiritual Administration of Muslims